Experimental Study of the Corrosiveness of Ternary Blends of Biodiesel Fuel - Milano J.; Umar H.; Shamsuddin A.H.; Silitonga A.S.; Irfan O.M.; Sebayang A.H.; Fattah I.M.R.; Mofijur M. (Frontiers Media S.A., 2023)
Austenitic stainless steel; Corrosion rate; Corrosion resistance; Diesel engines; Diesel fuels; Global warming; Oils and fats; Regression analysis; Scanning electron microscopy; Steel corrosion; Waste incineration; Automotive component; Calophyllum inophyllum; Corrosion analysis; Fuel properties; Fuel property analyse; Metallic material; Property analysis; Stainless steel 316; Ternary blends; Waste cooking oil; Biodiesel